Does the patient package insert (PPI) in South Africa serve the purpose of health communication? - Krige, Daleen; De Wet, Johann C. (Department of Communication Science, Unierstity of the Free State, 2008)
The aim of this article is to reflect on the usefulness and efficacy of the patient package insert (PPI) from the perspective of health communication. From the literature it is clear that American and European PPIs suffer a host of communication problems. What is the standing of the South African PPI with regard to its communication efficacy? Up till now there has been no published research on this aspect. The South African PPI is investigated for communication barriers, keeping the profile of a developing country in mind. The present research has indicated that PPIs in South African medication packages do not fulfil their communication aim, due to barriers that can be traced mainly to document and reader variables, rendering the communication contained in the document less efficient. Additionally, in the case of the PPI, health communication efficacy is influenced by, amongst others, cultural competence and understandability; factors that have been neglected in the South African PPI. Finally this article proposes improvements in order to enhance the value of the PPI as a means of effective health communication.
Keywords: Patient Package Insert; Health communication; South African PPI